Ocular Hypertension: A Review And Evidence-Based Roadmap - Rixon, Andrew John (Canadian Journal of Optometry, 2017)
Increased intraocular pressure is arguably the most important, and currently the only modifiable, risk factor for glaucomatous optic neuropathy. Ocular hypertension is often encountered by clinicians in daily practice and is expected to be seen with increasing frequency as the population ages. Awareness and understanding of the extensive research performed on this subject, with particular focus on the work of the Ocular Hypertension Study Group, are critical for comprehensively assessing the risk of conversion to glaucoma. Although management decisions can be complex, they can be aptly handled by the well-informed optometrist in consultation with their patients.